Critical success factors of project quality management system for Malaysian construction industry - Abdullah @ Mohd. Asmoni, Mat Naim (2015)
This study aims to explore the current implementation of Project Quality Management System and identify critical success factors of project quality management system associated with the indicators for each critical success factor identified. Hundreds of articles searched using keyword of “success factor”, “quality” and “construction” were gathered and analyzed using content analysis method. This research provides a comprehensive compilation of all previous study on the Critical Success Factors for Project Quality Management System implementation, through a clearly structured methodological approach. A total of six critical success factors for project quality management system in construction industry were identified. Each of the critical success factors is associated with three indicators that present evidences of implementation. The findings of this study provide guidance to the organization in implementing project quality.